Matriptase Induction of Metalloproteinase‐Dependent Aggrecanolysis In Vitro and In Vivo: Promotion of Osteoarthritic Cartilage Damage by Multiple Mechanisms - Wilkinson, David J. (Arthritis Rheumatol, 2017)
OBJECTIVE: To assess the ability of matriptase, a type II transmembrane serine proteinase, to promote aggrecan loss from the cartilage of patients with osteoarthritis (OA) and to determine whether its inhibition can prevent aggrecan loss and cartilage damage in experimental OA. METHODS: Aggrecan release from human OA cartilage explants and human stem cell–derived cartilage discs was evaluated, and cartilage‐conditioned media were used for Western blotting. Gene expression was analyzed by real‐time polymerase chain reaction. Murine OA was induced by surgical destabilization of the medial meniscus, and matriptase inhibitors were administered via osmotic minipump or intraarticular injection. Cartilage damage was scored histologically and aggrecan cleavage was visualized immunohistochemically using specific neoepitope antibodies. RESULTS: The addition of soluble recombinant matriptase promoted a time‐dependent release of aggrecan (and collagen) from OA cartilage, which was sensitive to metalloproteinase inhibition and protease‐activated receptor 2 antagonism. Although engineered human (normal) cartilage discs failed to release aggrecan following matriptase addition, both matrix metalloproteinase– and aggrecanase‐mediated cleavages of aggrecan were detected in human OA cartilage. Additionally, while matriptase did not directly degrade aggrecan, it promoted the accumulation of low‐density lipoprotein receptor–related protein 1 (LRP‐1) in conditioned media of the OA cartilage explants. Matriptase inhibition via neutralizing antibody or small molecule inhibitor significantly reduced cartilage damage scores in murine OA, which was associated with reduced generation of metalloproteinase‐mediated aggrecan cleavage. CONCLUSION: Matriptase potently induces the release of metalloproteinase‐generated aggrecan fragments as well as soluble LRP‐1 from OA cartilage. Therapeutic targeting of matriptase proteolytic activity reduces metalloproteinase activity, further suggesting that this serine proteinase may have potential as a disease‐modifying therapy in OA.